The Influence of Principals’ Technological Leadership and Teachers’ Digital Competence on The Readiness For Implementing Coding and Artificial Intelligence-Based Learning in Senior High Schools in Langowan District - Yully Kiroyan; Deitje Adolfien Katuuk; Romi Junior Mongdong (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of principals’ technological leadership and teachers’ digital competence on the readiness for implementing coding and artificial intelligence-based learning in senior high schools in Langowan District. Employing a quantitative approach with a survey method, the study involved 79 teacher respondents through questionnaire data collection that had been tested for validity and reliability. The data analysis technique used was multiple linear regression assisted by SPSS software. The results indicate that principals’ technological leadership has a positive and significant effect on implementation readiness. Furthermore, teachers’ digital competence is also proven to have a positive and significant effect on such readiness. Simultaneously, these two variables contribute a significant influence of 68.8% to the readiness for implementing coding and artificial intelligence-based learning. These findings conclude that strengthening technological leadership and enhancing teachers’ digital competence are strategic factors in successfully advancing educational transformation in the digital era